Hyperoxia improves autonomic function in individuals with long‐duration type 1 diabetes and macroalbuminuria. Issue 9 (20th May 2020) - Laursen, J. C.; Hansen, C. S.; Bordino, M.; Vistisen, D.; Zobel, E. H.; Winther, S. A.; Groop, P‐H.; Frimodt‐Møller, M.; Bernardi, L.; Rossing, P.
Abstract: Aim: Acute oxygen inhalation and slow deep breathing improve measures of autonomic function transiently in individuals with short‐duration type 1 diabetes. Our aims were to examine these interventions and changes in autonomic function in individuals with long‐duration type 1 diabetes and to explore interactions with the presence of macroalbuminuria or existing cardiovascular autonomic neuropathy. Methods: Individuals with type 1 diabetes ( n  = 54) were exposed to acute oxygen inhalation, slow deep breathing and a combination of both (hereafter 'the combination'). Primary outcomes were change in baroreflex sensitivity and heart rate variability. Associations between changes in outcomes were evaluated using mixed effects models. Results: Mean age ± sd was 60 ± 10 years and diabetes duration was 38 ± 14 years. Changes are presented as per cent difference from baseline with 95% confidence intervals. Acute oxygen inhalation, slow deep breathing and the combination increased baroreflex sensitivity by 21 (10, 34)%, 32 (13, 53)% and 30 (10, 54)%, respectively. Acute oxygen inhalation trended towards increasing heart rate variability 8 (−1, 17)% ( P  = 0.056), and slow deep breathing and the combination increased heart rate variability by 33 (18, 49)% and 44 (27, 64)% respectively. Macroalbuminuria or cardiovascular autonomic neuropathy did not modify results. Conclusion: Autonomic function is improved transiently in individuals with long‐duration type 1 diabetes and normoalbuminuria or macroalbuminuria by acute oxygen inhalation and slow deep breathing. There is a risk of survival bias. Autonomic dysfunction might be a reversible condition, and hypoxia might represent a target of intervention. What's new?: Cardiovascular autonomic dysfunction is a risk factor for mortality in type 1 diabetes. Hyperoxaemia can acutely improve autonomic function in individuals with short‐duration type 1 diabetes. We explored the potential for improving autonomic function in long‐duration type 1 diabetes with macroalbuminuria, and found that autonomic function could be improved. Autonomic dysfunction in type 1 diabetes might be a dynamic and reversible condition. Hypoxia might represent a target of intervention for attenuating progression of autonomic dysfunction in type 1 diabetes.